Piketty and the Political Origins of Inequality. (July 2021) - Lachmann, Richard; Brandon, Peter
Abstract: We examine Thomas Piketty's explanations for steady and rising inequality in the nineteenth and early twentieth centuries, the decline of inequality in the half-century after World War I, and the return of high levels of inequality since the 1970s. We specify empirical and conceptual problems with his analysis, which stem from his presentation of causality at a highly general and vague level. That leads him to confuse rather than clarify the causal relations among implacable economic forces, changes in technological innovation and population growth, ideology, and governmental policies and the outcomes that he seeks to explain. We identify social scientists and historians who are able to account for temporal and geographic variations in the political coalitions that propelled egalitarian reforms, and that in their absence cleared the terrain for reactionary anti-egalitarian policies that the rich incited for their narrow benefit. We explain why Piketty's limited conception of ideology is insufficient for explaining how mass opposition to inequality is mobilized. We show that if we want to combine the study of capital in the twenty-first century with that of politics, we need a broader conception of ideology than what Piketty offers, one that will allow us to specify how ideology affects parties, states, voters, and activists.